Implementasi Mata Pelajaran Pendidikan Agama untuk Pendidikan Berkelanjutan pada Sekolah Menengah Umum - Ismail Ismail; Muhammad Abrar Parinduri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to analyze the implementation of Islamic religious education subjects in supporting continuing education, especially in Public High Schools. The method used in this study uses a qualitative descriptive type. Data collection techniques are interviews and documentation. Data analysis techniques include data reduction, data presentation, conclusions, and verification. Data was collected through questionnaires distributed to 3 vice principals of student affairs in Medan City. The respondents of this study were students who had just completed their education at school with a total number of respondents as many as 204 people. The results showed that there were 27.17% of students answered ever and 26.08% answered never gained knowledge about continuing education. Then 46.73% of students have implemented continuing education. Then regarding whether students had ever made a visit related to environmental sustainability issues, the results showed that 64.2% of students answered that they had never made a visit related to environmental sustainability issues. The recommendation of this study is to appeal to religious education teachers and assisted by schools should always teach the importance of continuing education to students.